ClinicalKey E-Books. Issue 1 (2nd April 2020) - Stuart, Daniel
Abstract: Elsevier ClinicalKey is one of the industry's leading clinical search engines. Its database of diverse medical literature is informed by an e-book collection that forms a permanent part of its interface. A constituent part of the database's institutional site license, the collection seamlessly integrates with the database's other core resources through an efficient and clinician-friendly navigation. Content is delivered in a feasible manner that adapts to multiple platforms and incorporates personalized options to enrich the collection's versatility. Within libraries, the collection is highly valuable for clinical use or as an education resource.